Boeing: mitigating socio-political risks to the supply chain - Devinney, Timothy (Henry Stewart Talks, 2019)
This case study examines how Boeing’s supply chain for a single aircraft covers dozens of countries and states, so that governments worldwide would find it difficult to put pressure on Boeing or oppose purchasing of their products.